Analisis Posisi Bersaing dan Strategi Pemasaran Untuk Meningkatkan Penjualan Pada Nature Cake Denpasar Timur - Desiderius Milesantus Tena Witak; I Made Jamin Yasa; Ida Ayu Dinda Priyanka Maharani (WICAKSANA: Jurnal Lingkungan dan Pembangunan, 2024)
Nature Cake is a business that operates in the food sector, especially cakes. Where sales during 2023 will experience fluctuations. This research aims to analyze the company's competitive position, analyze the company's strengths, weaknesses, opportunities and threats and analyze the most relevant marketing strategies to increase sales value. This research was conducted on Nature Cake. Data sources consist of primary and secondary data. The data type consists of qualitative and quantitative data. Data analysis techniques use BCG analysis (Boston Consulting Group) and SWOT analysis (Strength, Weakness, Opportunity, Threats). The research results show that (1) Nature Cake's strengths include: skilled human resources, price, product quality, good and complete machines, service quality and promotional activities. Weaknesses include: limited production and products that do not last long. Opportunities include: being around residential areas, technological and cultural developments. Threats from Nature Cake include: company competition and quite tight price competition. The relevant strategy applied is the SO strategy because Nature Cake's position is between external opportunities and internal strengths in the SWOT matrix diagram.